Longitudinal variability of thermospheric zonal winds near dawn and dusk - Molina, Ivana; Scherliess, Ludger (Frontiers in Astronomy and Space Sciences, 2023)
Understanding the morphology and dynamics of the thermosphere is key to understanding the Earth’s upper atmosphere as a whole. Thermospheric winds play an important role in this process by transporting momentum and energy and affecting the composition, dynamics and morphology of not only the thermosphere but also of the ionosphere. The general morphology of the winds has been well established over the past decades, but we are only starting to understand its variability. In this process the lower atmosphere plays an important role due to direct penetration of waves from the lower atmosphere into the ionosphere/thermosphere, secondary waves generated on the way, or internal feedback mechanisms in the coupled ionosphere-thermosphere system. Therefore, knowledge about thermospheric variability and its causes is critical for an improved understanding of the global ionosphere-thermosphere system and its coupling to the lower atmosphere. We have used low- to mid-latitude zonal wind observations obtained by the Gravity Field and Steady-State Ocean Explorer (GOCE) satellite near 260 km altitude during geomagnetically quiet times to investigate the inter-annual and spatial zonal wind variability near dawn and dusk, during December solstice. The temporal and spatial variability is presented as a variation about the zonal mean values and decomposed into its underlying wavenumbers using a Fourier analysis. The obtained wave features are compared between different years and clear interannual changes are observed in the individual wave components, which appear to align with changes in the solar flux but do not correlate with variations in either El Niño Southern Oscillation or the Quasi Biennial Oscillation. The obtained wave features are compared and contrasted with results from the Climatological Tidal Model of the Thermosphere (CTMT) and revealed a very good agreement between CTMT and the 2009 and 2010 December GOCE zonal wind perturbations at dawn. However, during dusk, the CTMT zonal wind perturbations and in particular the zonal wave-1 component show significant differences with those observed by GOCE.